Effects of tabata body weight training on body fat percentage in obese women - Siti Maesaroh; Septyaningrum Putri Purwoto; Dendi Novendri (Universitas Suryakancana, 2022)
This study aims to prove the effect of an exercise protocol on the percentage of body fat tested in obese women. The samples of this study were 16 women, aged 19-21 years, had a Body Mass Index (BMI) = 25.0-29.9 kg/m² according to the Asia Pacific criteria. The sample was taken from the Department of Psychology, Faculty of Education (FIP), Surabaya State University (UNESA). This type of research uses a pre-experimental research design with